FROM THE FORMATION OF THE MYTH OF RACIAL DEMOCRACY TO THE ERA OF CONTEMPORARY CONSTITUTIONALISM: THE PRESSING NEED TO OVERCOME THE MERE FORMAL EQUALITY OF CF/88 (Revista Paradigma, 2025)
From the analysis of the myth of racial democracy from the historical and sociological perspectives, involved in the issues related to the adoption of the whitening policy adopted by the country and the demands supported by the black population, especially after the abolition of slavery, in the absence of policies public for the then newly "liberated" segment, this article presents the deconstruction carried out by "colonized" black thought, which has been presenting new critical perspectives and breaking with the discourse of racial domination that supported the process of "colonization" in Brazil ; and its connection with the current crisis of effectiveness of fundamental rights, given the symbolism of the Federal Constitution of 1988 regarding the right to racial equality, which demands the overcoming of the mere guarantee of equal legal treatment preached in the Magna Carta.
Keywords: 1.Racial Democracy. 2.Contemporary constitutionalism. 3.Democratic state.